Potensi hibridisasi antara ikan lele dumbo Clarias gariepinus dan ikan sembilang Plotosus canius - Henky Irawan (Intek Akuakultur, 2019)
In order for the descendants of North African catfish to have the ability to adapt to sea water, the broodstock of North African catfish must be hybridized with brooders of catfish species or relatives of catfish that live in sea water. Gray eel-catfish are the closest relatives of the Order with North African catfish that live in marine, brackish, freshwater, are in the waters and are amphidromous where they always move between fresh and sea water. Based on the size of egg cells and sperm cells, the eggs of Gray eel-catfish are larger than North African catfish eggs, allowing sperm cells to enter North African catfish eggs. Forms of physical properties are derived from males while adaptability is lowered from females, so that from the number of North African catfish chromosomes that are more than Gray eel-catfish, a combination that makes it possible to produce sea water catfish which means the physical body such as North African catfish and adaptability such as fish where sperm cells fit into the microfil hole are a combination of the male North African catfish pair with the Gray eel-catfish female. The results of the T test p value 0.98451, which shows there is no significant difference between male North African catfish morphometrics with male Gray eel-catfish, and female T test results p value 0.92264, which shows there is no significant difference between female North African catfish morphometrics and female Gray eel-catfish